Hydraulic investigation of the impacts of climate and land cover change on flooding of the Pinacanauan de Ilagan river in Isabela, Philippines - Yumol, Princesa Joel M.; Santos, Franz D. (Frontiers in Environmental Science, 2025)
In recent years, the Philippines has been experiencing more intense and frequent typhoons that often lead to damaging floods. Faced with the combined threat of climatic shifts and increasing urbanization, quantifying the effects of these future changes on flood risk to local communities is essential for effective disaster risk management efforts. This paper aims to assess the impacts of climate and land cover change on flood hazard parameters of the Pinacanauan de Ilagan River in Isabela using HEC-RAS (Hydraulic Engineering Center–River Analysis System). A comparison of model calculated flood depths and extents was performed using projected rainfall to represent future climate conditions and two different land cover estimates to represent changes in development of highly built-up areas. Results revealed that the change in land cover from 2015 to 2020 resulted in increases in maximum flood depths by as much as 12.83% with the greater depths found near the river confluences. Considering the increase in precipitation to represent future climate, maximum flood depths were found to increase by 19.79% signifying that climate has more pronounced effects on river flooding in the study area compared to change in land cover. These findings highlight the need for strategic planning of future developments to consider potential effects on flood risk along the Ilagan River. This study can also provide insights for local decision-makers on the potential impacts of climate change on flood risk management. Modelled flood parameters can be incorporated in the planning, design, and site selection of future evacuation facilities to improve disaster risk management strategies for local communities.